2006
DOI: 10.1074/jbc.m513625200
|View full text |Cite
|
Sign up to set email alerts
|

The Ectodomain of the Viral Receptor YueB Forms a Fiber That Triggers Ejection of Bacteriophage SPP1 DNA

Abstract: The irreversible binding of bacteriophages to their receptor(s) in the host cell surface triggers release of the naked genome from the virion followed by transit of viral DNA to the host cell cytoplasm. We have purified, for the first time, a receptor from a Gram-positive bacterium that is active to trigger viral DNA ejection in vitro. This extracellular region ("ectodomain") of the Bacillus subtilis protein YueB (YueB780) was a 7 S elongated dimer forming a 36.5-nm-long fiber. YueB780 bound to the tail tip of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
130
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 99 publications
(132 citation statements)
references
References 37 publications
(37 reference statements)
1
130
1
Order By: Relevance
“…Interestingly, essentially the same pattern of EsaA crosslinks was seen whether EssA, EssB or EssC were absent, suggesting that the crosslinked products did not contain any of these proteins. It has been reported that the long extracellular domain of YueB, the Bacillus subtilis homologue of EsaA, forms a highly elongated homo‐dimer 17 and it is therefore likely that the crosslinks seen here correspond to different conformers of a crosslinked EsaA dimer.…”
Section: Resultsmentioning
confidence: 82%
“…Interestingly, essentially the same pattern of EsaA crosslinks was seen whether EssA, EssB or EssC were absent, suggesting that the crosslinked products did not contain any of these proteins. It has been reported that the long extracellular domain of YueB, the Bacillus subtilis homologue of EsaA, forms a highly elongated homo‐dimer 17 and it is therefore likely that the crosslinks seen here correspond to different conformers of a crosslinked EsaA dimer.…”
Section: Resultsmentioning
confidence: 82%
“…In Gram-negative (Gram Ϫ ) bacteria (e.g., Escherichia coli), this is observed with phages binding to porins, such as phage T5 (68,69) or phage . In Gram ϩ bacteria, this tail fiber is observed in phage SPP1 (45,66) and lactococcal phage c2 (70), which bind to extracellular components of the type 7 secretion system (T7SS), called, respectively, YueB (66) and PIP (70). In contrast, lactococcal phages of the 936 and P335 families seem to attach exclusively to polysaccharides and bear at their tail end a large macromolecular entity called the baseplate.…”
Section: Discussionmentioning
confidence: 99%
“…The N terminus, loop ␤2␤2Ј, loop ␤3␤4, and loop ␤6␤7 are located close to gp15, whereas loop ␤2Ј␤3 fills the stopper EM density on the tail side. Incubation of SPP1 with the ectodomain of its cellular receptor (YueB780) (19) leads to efficient DNA release from wild-type phages and virions carrying gp16 with single cysteine mutations, apart from a minor inhibitory effect in case of gp16 Q51C (Fig. 5D).…”
Section: Engineering Of Disulfide Intersubunit Bridges Between Stoppementioning
confidence: 99%
“…We then investigated the effect of covalent intersubunit cross-linking of the stopper in viral genome ejection using a DNase protection assay that quantifies nonejected DNA (9,19).…”
Section: Engineering Of Disulfide Intersubunit Bridges Between Stoppementioning
confidence: 99%
See 1 more Smart Citation